PENYULUHAN PENGELOLAAN KEUANGAN RUMAH TANGGA DAN PENGGUNAAN APLIKASI PENGATUR KEUANGAN DIGITAL - Siti Nuke Nurfatimah; Enung Nurhayati (Jurnal Abdimas Bina Bangsa, 2023)
This community service aims to provide counseling and assistance to housewives in Sembawa Village regarding planning and managing household finances. In addition, we have also introduced several digital financial applications that can be used by individuals to be able to record household finances at any time. The problems faced by these housewives are the difficulty in managing finances, especially cash flow during the Covid 19 Pandemic and the low level of technology utilization to control household finances. The method chosen was counseling and mentoring with a total of 20 participants coming from housewives who did not work and PKK cadre mothers and the place of implementation was at the Sembawa Village Hall, Kuningan Regency. The result of this community service activity is that there is an increase in knowledge and insight regarding financial planning and management in theory being able to compile financial budgets and keep financial records of financial management carried out both manually and digitally